Z badań nad neolitem i wczesną epoką brązu na Pojezierzu Gostynińskim: Wstępne wyniki badań w Stefanowie, stan. 4, gm. Gostynin, woj. płockie, i Grabinie, stan. 5, gm. Łąck, woj. płockie - Rybicka, Małgorzata; Gowin, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The first systematic excavations of sites from the Neolitic and Early Bronze Age in the Gostynin Lake District situated between Włocławek and Płock were not conducted until 1987-1988. They were preceded by the surface surveys which disclosed a comparatively rich network of settlement points from these periods. Excavations were conducted in two sites: the settlement of the Funnel Beaker culture in Stefanów site A, gm. Gostynin, woj. Płock and multicultural site 5 in Grabina, gm. Gostynin, woj. Płock. Stefanów, site 4, gm. Gostynin, woj. Płock. The site is situated by a former small stream (fig. 1). An excavation of 2 330 m was opened during the surveys (fig. 2). A small amount of stone artefacts, pugging, fragments of bones and a collection of clav vessels fragments (1170) were obtained. We can ascribe 969 fragments of pottery (including 128 distinctive fragments) to the Funnel Beaker culture. The analysis of these remains enabled to distinguish two basic stylistic groups defining the chronological position of the settlement in Stefanów. The first one joins the previously discussed site with the Luboń phase of the Funnel Beaker culture (tabl. I, 1-3) which confirms preliminary analysis vessel forms. The secound one indicates that it has some connection with the Baden (or Baden - Pécel) culture (tabl. I, 1, A, 5). In the Luboń phase of the Funnel Beaker culture, the Radziejów group developed in the neighbourhood of the Gostynin Lake District in Kujawy. The so called "Baden pottery" of this group is not only stylistically different, but also its technology is quite unlike the traditional. At the present stage of the surveys it is possible to exclude the impact of the Gostynin Lake District in transmitting "Baden" features to Kujawy region. Besides, about 200 fragments of pottery (including 20 characteristic fragments) connected with the Early Bronze Age were obtained. It is hard to state the cultural attachment of this set. Two groups of pottery can be distingiushed in the material. One of them contains fragments of mid and thin walls of vessels (tabl. I, 6-8). The secound group comes most likely from one thick walled vessel (tabl. I, 9). It is also possible that this differentiation within the set is a result of functional (not cultural) differences. Grabina, site 5, gm. Łąck. This site is situated at the slope of the gully the bottom of which is occupied by two lakes: Górskie and Ciechomickie. From two excavations, covering the 2 area of 15 m2 , a set of 155 fragments of pottery and 395 flint artefacts were obtained. These materials are partly mixed. Late Palaeolithic (tabl. II, 1-3), Late Mezolithic (tabl. II, 4-8), Neolithic (tabl. II, 9) flint artefacts were distinguished preliminary. The pottery represents the Funnel Beaker culture, the cultures of the Forest Zone and the Early Bronze Age. These remains come from both the layer and the three objects of settlement. Through view on the complex problem of the premaeval history of the Gostynin Lake District will bee reached after some further archeological surveys and investigations. Both the separate character of the environment and the localization of the previously area, likewise the obtained materials let us expect interesting cultural phenomena.